Muhammad Abduh's reformism: The modes of its dissemination in preindependent Malaysia - Zakariya, Hafiz (2019)
Muhammad 'Abduh played an important role in the transfornation of Muslim society in the Arab world.He contributed immensely in shaping the education and societal.development. This paper examines the diffusion of 'Abduh's reformism in the Malay peninsula during the early twentieth century.